Differentiation of Neisseria gonorrhoeae isolates requiring proline, citrulline, and uracil by plasmid content, serotyping, and pulsed-field gel electrophoresis. - Ng, L K (1995)
A combination of DNA macrorestriction analysis using pulsed-field gel electrophoresis and a serotyping method using three panels of monoclonal antibody was used to discriminate 43 epidemiologically unrelated Neisseria gonorrhoeae isolates requiring proline, citrulline, and uracil (PCU-) into 35 groups. This indicates that PCU- isolates of N. gonorrhoeae are not clonal.